PENGENALAN CARA PENGGUNAAN TEKNOLOGI INFORMASI SCREEN TIME PARENTAL CONTROL KEPADA ORANG TUA DALAM PENGONTROLAN PENGGUNAAN ANDROID PADA ANAK - Noni Rahmawati; Rio Rahmadani; Tomi Kurniawan; Agus Nurofik; Nini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Obligations to every lecturer in Higher Education as described in the Tridharma of Higher Education are Education, Research, and Community Service. One of these obligations as a lecturer at the Nahdatul Ulama Jambi Institute of Technology and Science will carry out Community Service, this is carried out in connection with the concern of every institution or institution engaged in education, especially higher education by following developments and technological advances, especially the city of Jambi which has the potential to enter various types of technology, especially android cellphones, both legal and non-legal so that it is easy to get cellphones of various types of brands at low prices in the city of Jambi, so many parents buy android cellphones for children to increase knowledge in the field of education, but along with the busyness of parents so that the use of this android cellphone is not controlled and its use is widely misused not only to increase knowledge but also to play games that spend time from morning to night sometimes don't remember the time, where children today busy playing games, not focusing on school, the world of physical play which can make children become abnormal (such as autism) do not care about their parents and their environment, for that we have a concern to provide technology knowledge and applications to parents in restricting children from using the android mobile phone by organizing Community Service activities.